«EL GOZE DE LOS DERECHOS DE CIUDADANO»: ELECTIONS AND CITIZENSHIP IN CENTRAL AMERICA, CA. 1770-1850 - Dym , Jordana (2021)
Between 1808 and 1850, the provinces and then independent Central American states organized hundreds of elections. This article examines the electoral theory set out in the region’s constitutions and electoral regulations and explores the implementation as shown in election books, voter lists, newspapers, correspondence, and other documents that reveal voting and political practices at the municipal, state, and federal levels. The analysis shows that the surprising result of a system that privileged indirect voting and the power of the legislative body to impose results was a substantial citizen commitment to active political participation that ultimately prepared the region to expand citizen rights (at least on paper) in the second half of the nineteenth century.